Unbalanced serum immunoglobulins in clinical subtypes of pediatric tuberculosis disease - Consonni, Filippo; Chiti, Nicolò; Ricci, Silvia; Venturini, Elisabetta; Canessa, Clementina; Bianchi, Leila; Lippi, Francesca; Montagnani, Carlotta; Giovannini, Mattia; Chiappini, Elena; Galli, Luisa; Azzari, Chiara; et al. (Frontiers in Pediatrics, 2022)
Immune response to tuberculosis (TB) has been extensively studied in the past decades and classically involves cellular immunity. However, evidence suggests that humoral immunity may play a relevant role. Past studies regarding serum immunoglobulin (Ig) levels in TB are dated and only involve adult subjects. In this study, we retrospectively studied a cohort of 256 children with TB disease and analyzed 111 patients screened for total serum Ig at diagnosis. According to the severity and extent of organ involvement, subjects were divided into four groups, namely, uncomplicated pulmonary TB (UCPTB, 56.3% of patients), complicated pulmonary TB (CPTB, 22.5%), lymph node extrapulmonary TB (LN-EPTB, 7.2%), and extra-nodal extrapulmonary TB (EN-EPTB, 13.5%). Serum IgG and IgA levels were significantly higher in more severe and extended TB disease. Median IgG levels progressively increased from uncomplicated to complicated pulmonary and nodal forms, reaching their highest values in diffuse extra-pulmonary TB. In parallel, UCPTB showed significantly lower frequencies of patients presenting a substantial increase in IgG levels when compared with the other three groups. No relevant differences in IgM levels were detected. Ig screening at follow-up showed a significant reduction in IgG and IgA levels. Finally, we unveiled three cases of selective IgA and one case of selective IgM deficiencies (SIgMD), the latter with a severe clinical course. Serum IgG and IgA may be a useful clinical tool to assess the severity and monitor the treatment response in pediatric TB disease. Moreover, immunological workup in children with TB disease may unmask primary defects of humoral immunity.